2020
DOI: 10.1021/acs.jctc.9b01208
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Evaluation of Fourteen Docking Programs on Protein–Peptide Complexes

Abstract: A large number of protein−protein interactions (PPIs) are mediated by the interactions between proteins and peptide segments binding partners, and therefore determination of protein−peptide interactions (PpIs) is quite crucial to elucidate important biological processes and design peptides or peptidomimetic drugs that can modulate PPIs. Nowadays, as a powerful computation tool, molecular docking has been widely utilized to predict the binding structures of protein−peptide complexes. However, although a number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
83
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(85 citation statements)
references
References 46 publications
0
83
0
Order By: Relevance
“…ADCP, which currently allows consistent docking of peptides with up to 20 amino acids 25 (Figure 7), is at the cutting edge of this field in a recent evaluation of 14 peptide docking programs. 61 ADCP can also cyclize peptides head-to-tail ( Figure 7a) and/or by forming up to two disulfide bridges when cysteines are present (Figure 7b) thus supporting molecules with multiple cycles. 27 Cyclization is achieved on-the-fly during the docking simulation by using potentials to pull the N-and C-termini or cysteine sulfur atoms together while ignoring steric repulsion between these atoms.…”
Section: Peptide Dockingmentioning
confidence: 99%
See 1 more Smart Citation
“…ADCP, which currently allows consistent docking of peptides with up to 20 amino acids 25 (Figure 7), is at the cutting edge of this field in a recent evaluation of 14 peptide docking programs. 61 ADCP can also cyclize peptides head-to-tail ( Figure 7a) and/or by forming up to two disulfide bridges when cysteines are present (Figure 7b) thus supporting molecules with multiple cycles. 27 Cyclization is achieved on-the-fly during the docking simulation by using potentials to pull the N-and C-termini or cysteine sulfur atoms together while ignoring steric repulsion between these atoms.…”
Section: Peptide Dockingmentioning
confidence: 99%
“…We are currently tackling these challenges by exploring simplified representations of the conformational space based on backbone crankshaft transformations 26 (Figure 3). ADCP, which currently allows consistent docking of peptides with up to 20 amino acids 25 (Figure 7), is at the cutting edge of this field in a recent evaluation of 14 peptide docking programs 61 . ADCP can also cyclize peptides head‐to‐tail (Figure 7a) and/or by forming up to two disulfide bridges when cysteines are present (Figure 7b) thus supporting molecules with multiple cycles 27 .…”
Section: Peptide Dockingmentioning
confidence: 99%
“…Typical hydrophobic face is not seen in Lead 1, 3 and 4 though it seems to be in W1, W2 and L2 ( Figure 7C). As emphasized before, the 4 distinct isomers were determined and selected by the experiential thresholds of RMSD and binding affinity 36,40 though there were no statistical differences of RMSD and binding affinity among the isomers and wild types ( Figure 8). In line with early studies 42 , various physicochemical properties were found in the millions of isomers (data not shown).…”
Section: Retrospective Comparison Of the Isomer Inhibitor And The Cormentioning
confidence: 99%
“…Using the reference ligands and the docking receptor SARS-CoV-2 S chain E ( Figure 4B, 4D-E), individual affinity maps were computed by the ARDF model in AutoDock CrankPep. As shown in Figure 5 and in Table S2 Supplementary data, following 618 docking assays (all dots), 4 peptide ligands (red dots) were finally determined as the most promising leads against SARS-CoV-2 S because the mean values of all atoms Root-Mean-Square Deviation (RMSD) and binding affinity were less than 2.5 Å and -10 kcal/mol respectively among all the first 10 docking ranks 36,40 . These outputs were the first demonstration of the effective binding activities between RBMs-hACE2 isomers and SARS-CoV-2 S and suggested that these 4 peptide isomers retained inhibitory potentials against SARS-CoV-2 infection.…”
Section: Application Of a Peptide-protein Docking Approach For Validamentioning
confidence: 99%
See 1 more Smart Citation